Chronic Chagas Cardiomyopathy Patients and Resynchronization Therapy: a Survival Analysis - Menezes Junior, Antônio da Silva (Braz J Cardiovasc Surg, 2018)
INTRODUCTION: Chagas disease represents an important health problem with socioeconomic impacts in many Latin-American countries. It is estimated that 20% to 30% of the people infected by Trypanosoma cruzi will develop chronic Chagas cardiomyopathy (CCC), which is generally accompanied by heart failure (HF). Cardiac resynchronization therapy (CRT) may be indicated for patients with HF and electromechanical dysfunctions. OBJECTIVE: The primary endpoint of this study was to analyze the response to CRT in patients with CCC, while the secondary endpoint was to estimate the survival rates of CRT responder patients. METHODS: This is an observational, cross-sectional and retrospective study. The records of 50 patients with CRT pacing devices implanted between June 2009 and March 2017 were analyzed. For statistical analyses, Pearson's correlation was used along with Student's t-test, and survival was analyzed using the Kaplan-Meier method. A P value of <0.05 was considered significant. RESULTS: Out of 50 patients, 56% were male, with a mean age of 63.4±13.3 years and an average CRT duration of 61.2±21.7 months. The mean QRS duration was 150.12±12.4 ms before and 116.04±2.2 ms after the therapy (P<0.001). The mean left ventricular ejection fractions (LVEF) were 29±7% and 39.1±12.2% before and after CRT, respectively (P<0.001). A total of 35 (70%) patients had a reduction of at least one New York Heart Association (NYHA) functional class after six months of therapy (P=0.014). The survival rate after 72 months was 45%. CONCLUSION: This study showed clinical improvement and a nonsignificant survival rate in patients with CCC after the use of CRT.